Analisis Kasus Perdagangan Manusia: Buruh Migran Timor di Malaysia berdasarkan Pendekatan Eleanor Roosevelt tentang Hak Asasi Manusia - Hendrik Fahik; Yohanes I Wayan Marianta; Kunibert Janson Seran (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
Here is the English translation of your text: This study aims to analyze a human trafficking case involving Timorese migrant workers in Malaysia using the human rights approach developed by Eleanor Roosevelt. This approach emphasizes the importance of protecting, respecting, and fulfilling the fundamental rights of every individual, particularly those in vulnerable positions. In this study, a qualitative research method is employed with a case study approach, which includes document analysis, in-depth interviews with stakeholders, and participatory observation of the conditions of the migrant workers. The research findings indicate that Timorese migrant workers often fall victim to various forms of exploitation, such as forced labor, inhumane working conditions, unfair wages, and minimal legal protection from both the sending and receiving countries. This situation reflects a serious violation of the fundamental principles of human rights. This study makes an important contribution to uncovering the ongoing dynamics of human trafficking in Southeast Asia, particularly targeting migrant labor groups. Furthermore, the findings provide several policy recommendations, including the need for stronger bilateral agreements between labor-sending and labor-receiving countries, increased oversight of recruitment agencies, and human rights education for prospective migrants. Thus, it is hoped that the protection of Timorese migrant workers can be significantly improved.